2013
DOI: 10.1002/da.22077
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Post-Injury Mental Health Problems

Abstract: Serious nonfatal physical injuries and burns are common occurrences that can have substantial implications for personal, social, and occupational functioning. Such injuries are frequently associated with significant mental health issues, and compromised quality of life and well-being. The purpose of this review is to summarize the current literature on physical, psychological, and social risk factors for mental health issues post-injury and to contextualize findings using Engel's biopsychosocial framework. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
85
4
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(123 citation statements)
references
References 79 publications
(164 reference statements)
30
85
4
4
Order By: Relevance
“…Risk factors for post-injury depression in our study were consistent with the previous studies: female gender, injury severity, and higher levels of perceived stress or pain [14,34,35]. Although female workers tend to get depressed more after an injury, our subgroup analysis by gender revealed a relatively higher impact of occupational injury on depression in males.…”
Section: Discussionsupporting
confidence: 91%
“…Risk factors for post-injury depression in our study were consistent with the previous studies: female gender, injury severity, and higher levels of perceived stress or pain [14,34,35]. Although female workers tend to get depressed more after an injury, our subgroup analysis by gender revealed a relatively higher impact of occupational injury on depression in males.…”
Section: Discussionsupporting
confidence: 91%
“…Depression was defined as one or more hospitalizations with a diagnosis for depressive disorder, affective psychoses, neurotic depression, or adjustment reaction (ICD-9-CM codes 296.2Y296. 8 , or one or more physician visits with a diagnosis for anxiety disorders (ICD-9-CM code 300) and one or more prescriptions for an antidepressant or mood stabilizer (Anatomical Therapeutic Chemical codes N03AB02, N03AB52, N03AF01, N05AN01, N06A). SUD was defined as one or more hospitalizations or physician visits with a diagnosis for alcohol or drug psychoses, alcohol or drug dependence, or nondependent abuse of drugs (ICD-9-CM codes 291, 292, 303Y305; ICD-10-CA codes F10YF19, F55).…”
Section: Definitions Of Covariatesmentioning
confidence: 99%
“…5Y7 A recent psychosocial model has been proposed to help frame these interactions. 8 Recent studies have demonstrated an association between various traumatic events and suicidal behavior. 9Y11 A recent study in Swedish teenagers with an injury visiting an emergency department found an increased risk for subsequent premature death (1.44 standardized mortality ratio) compared with the reference population, with suicide accounting for 32% of these deaths.…”
mentioning
confidence: 99%
“…A depressão pode afetar negativamente a recuperação e reabilitação da vítima de acidente por suprimir a função do sistema imunológico ou diminuir a motivação para participar dos programas de reabilitação (SAREEN et al, 2013).…”
Section: Depressãounclassified
“…Problemas de saúde mental, como depressão, podem ser uma reação a deficiências físicas que acompanham a lesão, dada às significativas perdas que podem ocorrer e a falta de controle sobre o próprio corpo e o ambiente (SAREEN et al, 2013). É destacado na literatura internacional que o apoio social tem fator preponderante na prevenção dos sintomas de depressão no pós-trauma (SAREEN et al, 2013). Segundo os autores o apoio emocional, a aceitação da família e dos amigos pode ajudar a amortecer o estresse associado ao trauma e facilitar a resiliência e o ajuste no pós-trauma.…”
Section: Depressãounclassified